2018
DOI: 10.1021/acs.jmedchem.7b01575
|View full text |Cite
|
Sign up to set email alerts
|

Small-Molecule Activator of UNC-51-Like Kinase 1 (ULK1) That Induces Cytoprotective Autophagy for Parkinson’s Disease Treatment

Abstract: UNC-51-like kinase 1 (ULK1), the yeast Atg1 ortholog, is the sole serine-threonine kinase and initiating enzyme in autophagy, which may be regarded as a target in Parkinson's disease (PD). Herein, we discovered a small molecule 33i (BL-918) as a potent activator of ULK1 by structure-based drug design. Subsequently, some key amino acid residues (Arg18, Lys50, Asn86, and Tyr89) were found to be crucial to the binding pocket between ULK1 and 33i by site-directed mutagenesis. Moreover, we found that 33i induced au… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
48
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(48 citation statements)
references
References 49 publications
0
48
0
Order By: Relevance
“…The induction of protective autophagy to inhibit apoptosis is one of the reasons for the development of drug resistance in tumor cells during therapy [207]. Some small molecule drugs targeting ULK1 show inhibitory effects on ULK1 expression and the activity of autophagy, and cause tumor cells to be more sensitive to chemotherapeutic drugs [136,208]. It has been reported that overexpression of ULK1 is inversely related to the prognosis of various tumors, such as colon cancer, breast cancer, lung cancer, nasopharyngeal cancer, and esophageal cancer [136].…”
Section: Small Molecule Drugs Targeting Ulk Reverse Tumor Resistancementioning
confidence: 99%
“…The induction of protective autophagy to inhibit apoptosis is one of the reasons for the development of drug resistance in tumor cells during therapy [207]. Some small molecule drugs targeting ULK1 show inhibitory effects on ULK1 expression and the activity of autophagy, and cause tumor cells to be more sensitive to chemotherapeutic drugs [136,208]. It has been reported that overexpression of ULK1 is inversely related to the prognosis of various tumors, such as colon cancer, breast cancer, lung cancer, nasopharyngeal cancer, and esophageal cancer [136].…”
Section: Small Molecule Drugs Targeting Ulk Reverse Tumor Resistancementioning
confidence: 99%
“…Autophagy is a cellular mechanism that recycles materials such as abnormal proteins and damaged organelles to maintain cell survival and homeostasis. The alteration of autophagy may be a key factor contributing to the pathogenesis of PD 15 , and a number of reports showed that increased autophagy has potential therapeutic effects in PD 16,17 . In the present study, we investigated whether and how Exos repair the damage of PD models in vitro and in vivo by regulating autophagy.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, several pieces of evidence suggest that autophagy plays an important role in neurogenic disorders, such as HD, PD, Alzheimer's, and amyotrophic lateral sclerosis (Karabiyik, Lee, & Rubinsztein, 2017;Ouyang et al, 2018;Shi et al, 2012). However, other studies have shown that excessive autophagy could be related to neuronal death in cerebral ischemia (Fornai et al, 2008;Kabuta, Suzuki, & Wada, 2006;Shi et al, 2012).…”
Section: Ormond Et Al In a Study Used Stem Cells Alone Or In Combinamentioning
confidence: 99%